2018
DOI: 10.1158/1078-0432.ccr-17-1901
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations in Calcitonin Receptor (CALCR) Identify Highly Aggressive Glioblastoma with Poor Outcome

Abstract: Despite significant advances in the understanding of the biology, the prognosis of glioblastoma (GBM) remains dismal. The objective was to carry out whole-exome sequencing (WES) of Indian glioma and integrate with that of TCGA to find clinically relevant mutated pathways. WES of different astrocytoma samples ( = 42; Indian cohort) was carried out and compared with that of TCGA cohort. An integrated analysis of mutated genes from Indian and TCGA cohorts was carried out to identify survival association of pathwa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 35 publications
0
32
0
1
Order By: Relevance
“…Analysis of the top two modules from the PPI network indicated that GBM was associated with the cell cycle and neuroactive ligand-receptor interaction. Pal et al (32) recently demonstrated that patients who have GBM in combination with a defective neuroactive ligand-receptor interaction pathway have a poor prognosis (P<0.0001). Therefore, monitoring these signaling pathways may help predict tumor occurrence and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the top two modules from the PPI network indicated that GBM was associated with the cell cycle and neuroactive ligand-receptor interaction. Pal et al (32) recently demonstrated that patients who have GBM in combination with a defective neuroactive ligand-receptor interaction pathway have a poor prognosis (P<0.0001). Therefore, monitoring these signaling pathways may help predict tumor occurrence and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Мутации в рецепторе кальцитонина (CALCR) выявляют высокоагрессивные глиобластомы с летальным результатом у человека. И все же можно констатировать, что экзогенно добавленный кальцитонин ингибировал различные свойства клеток глии и сигнальных путей рецептора [56].…”
Section: взаимодействие гормонов с рецепторамиunclassified
“…Other recent reports show variable expression of CALCR mRNA with expression in only a subset 12/42 [26] or 115/152 [27] of primary tumours. In addition, Pal et al [28] report a correlation between patient survival and non-synonymous mutations in CTR.…”
Section: Introductionmentioning
confidence: 99%